Identifikasi Persamaan Plant Ball and Beam Tanpa Tuas - Erwani Merry Sartika; T. Rudy Sarjono; Jeremy Jonathan (Universitas Tarumanagara, 2019)
The equation of the ball and beam plant model has a lot of research. Generally, ball and beam plants use a lever on the part that is connected to the motor. In this paper plant ball and beam is used without a lever. The lever is changed by a circle that is moved not through the center so that it can raise and bring down the beam through the side of the circle which causes changes in the motorservo position to the movement of the ball becomes non-linear. For this reason, the equation of the existing ball and beam plant cannot be used to represent the characteristics of the plant. In this paper, ball and beam plants without levers were identified using the least square method to obtain the model equation.The least square method was successfully used to identify the model of plant ball and beam without a lever in the form of a second-order equation consisting of 2 poles and 1 zero with a validation value (loss function) of 0.1220 Persamaan model plant ball and beam telah banyak yang meneliti. Umumnya plant ball and beam menggunakan tuas di bagian yang terhubung pada motor. Pada makalah ini digunakan plant ball and beam tanpa tuas. Tuas diubah dengan lingkaran yang digerakkan tidak melalui pusat sehingga dapat menaikkan dan menurunkan beam melalui sisi lingkaran tersebut yang menyebabkan perubahan posisi motorservo terhadap pergerakan bola menjadi tidak linier. Dengan alasan tersebut maka persamaan plant ball and beam yang sudah ada tidak dapat digunakan untuk mewakili karakteristik plant tersebut. Pada makalah ini plant ball and beam tanpa tuas di identifikasi menggunakan metode least square untuk mendapatkan persamaan model. Metode least square berhasil digunakan untuk mengidentifikasi model plant ball and beam tanpa tuas berupa persamaan orde dua yang terdiri dari 2 pole dan 1 zero dengan nilai validasi (loss function) sebesar 0.1220.